2018
DOI: 10.2147/ott.s171212
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo superior radiosensitizing effect of berbamine for head and neck squamous cell carcinoma

Abstract: BackgroundBerbamine (BBM), one of the bis-benzylisoquinoline products isolated from Berberis amurensis, has been demonstrated for its anticancer effect against leukemia, breast cancer, liver cancer, etc. There are some studies focusing on the chemosensitization effect of BBM. However, there is no report about whether BBM could enhance the anticancer effect of radiation, which made us to explore the possible radiosensitization effect of BBM.Materials and methodsHere, in vitro cytotoxicity of BBM was evaluated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Additionally, berbamine exerted antitumor effects in vitro and in vivo through apoptosis induction partially relevant to the activation of the p53 gene in colorectal cancer [ 8 ]. Moreover, berbamine enhanced the efficacy of gefitinib in pancreatic cancer cells and radiosensitivity for head and neck squamous cell carcinoma by inhibiting the STAT3 pathway [ 40 , 41 ]. Herein, we attempted to unambiguously investigate the effects and potential mechanisms of berbamine in bladder cancer in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, berbamine exerted antitumor effects in vitro and in vivo through apoptosis induction partially relevant to the activation of the p53 gene in colorectal cancer [ 8 ]. Moreover, berbamine enhanced the efficacy of gefitinib in pancreatic cancer cells and radiosensitivity for head and neck squamous cell carcinoma by inhibiting the STAT3 pathway [ 40 , 41 ]. Herein, we attempted to unambiguously investigate the effects and potential mechanisms of berbamine in bladder cancer in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies, both in vivo and in vitro, which show that the majority of brain tumors are resistant to ionizing radiation treatment. Fractionation used in standard radiotherapy for glioma treatment comprises a total 45–60 Gy dose, administered in 1.8–2 Gy per fraction over a 5–6 weeks interval, while the most preclinical studies use a radiation dose that does not exceed 10 Gy [12,13,14,18,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that BBM possesses biological activities including anti-oxidation, anti-inflammation and protective effects against ischemia/reperfusion injury ( 9 11 ). In addition, BBM exhibits anti-tumor activity and inhibits the proliferation of breast cancer cell lines ( 8 , 12 ). Although previous studies have demonstrated that BBM downregulates the protein levels of Bax and Bcl-2 ( 12 ), the molecular mechanism underlying its anti-tumor function is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BBM exhibits anti-tumor activity and inhibits the proliferation of breast cancer cell lines ( 8 , 12 ). Although previous studies have demonstrated that BBM downregulates the protein levels of Bax and Bcl-2 ( 12 ), the molecular mechanism underlying its anti-tumor function is still unclear. In addition, few studies have explored the effects and mechanism of BBM in breast cancer.…”
Section: Introductionmentioning
confidence: 99%